2022
DOI: 10.3390/foods11081107
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Antioxidant Properties of Moringa oleifera Leaves in Functional Foods

Abstract: Moringa oleifera is a tree cultivated originally in northern India, whose ancient use as a medicine has demonstrated its antioxidant and anti-inflammatory properties. Due to its richness in minerals and macronutrients, the antioxidant capacity and the mineral bioaccesibility were assessed. In addition, the chemical composition, amino acid, fatty acid, and mineral content were also evaluated. The performed analysis reported a high content of proteins and low content of lipids in the chemical composition. Regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 63 publications
6
44
11
2
Order By: Relevance
“…Nevertheless, a huge variation in the data exists which is related with factors previously discussed [ 40 ]. For example, Peñalver et al [ 49 ], observed an average Mn concentration of 72.1 mg/kg, a value very close to ours, while their Ca levels do not reach 15000 mg/kg. Kumssa et al [ 33 ] measured 18300 mg/kg Ca while our data has an average value of 24000.…”
Section: Resultssupporting
confidence: 88%
“…Nevertheless, a huge variation in the data exists which is related with factors previously discussed [ 40 ]. For example, Peñalver et al [ 49 ], observed an average Mn concentration of 72.1 mg/kg, a value very close to ours, while their Ca levels do not reach 15000 mg/kg. Kumssa et al [ 33 ] measured 18300 mg/kg Ca while our data has an average value of 24000.…”
Section: Resultssupporting
confidence: 88%
“…Antioxidant‐rich moringa leaves mainly possess isothiocyanates responsible for the anticarcinogenic, antidiabetic, and antibiotic properties of the leaf. The presence of a balanced level of amino acids, vitamins (Vit A, C), and antioxidants make the moringa leaves a potential ingredient for the formulation of functional foods (Awad et al, 2022; Peñalver et al, 2022; Singh et al, 2015). Phytochemicals or polyphenolic compounds like flavonoids, saponins, alkaloids, sterols, tannins, and reducing sugars are present in moringa together with anticarcinogenic agents such as glucosinolates, glycoside compounds, and isothiocyanates (Gandji et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 26 Similarly, MO leaves extract seemed to have a potential cognitive enhancer via the decreased oxidative stress and the enhanced cholinergic function. 24 , 25 , 54 , 55 …”
Section: Discussionmentioning
confidence: 99%
“…26 Similarly, MO leaves extract seemed to have a potential cognitive enhancer via the decreased oxidative stress and the enhanced cholinergic function. 24,25,54,55 In our study, we evaluated the activity of AChE and mRNA expression level of BDNF in hippocampus tissue of the mice. Central cholinergic system particularly in hippocampus plays a significant role in regulation of learning and memory, and it was reported that chronic predictable stress influenced the AChE activity in hippocampus along with the impairment of cognitive function.…”
mentioning
confidence: 99%